ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA PADA MATERI GEOMETRI DI KELAS XII MAS MODERN ARAFAH - andina, Andina; Erita, Selvia (JURNAL MathEdu (Mathematic Education Journal), 2024)
ter and area of ​​flat shapes in the f Geometry is a branch of mathematics that is taught with the aim of enabling students to understand the properties and relationships between geometric elements and to encourage students to think critically and solve problems in everyday life. This research aims to analyze the difficulties of class XII MAS Modern Arafah students in answering geometry questions. This research uses an exploratory study in the form of a written description test on geometry material given to 10 students of XII MAS Modern Arafah. The results of the analysis show that there are difficulties faced by students in answering geometry questions, these difficulties include (1) students have difficulty using concepts, (2) students have difficulty understanding the material, and (3) students have difficulty solving verbal problems. The results of this research can be used as material for developing geometric problems, especially regarding the perimeter and area of ​​flat shapes in the future. uture.